تصميم نظام مقترح لمراقبة سير العمليات الانتاجية في المنشات الصناعية: بالتطبيق في مصنع الغزل والنسيج بالموصل - صباح انور اليونس (PROSPECTIVE RESEARCHES, 2005)
A system for observing production operations has been designed in order to be applied in any industrial institution. It can also be applied in service institutions. The system uses a number of small cameras which are fixed in specific places inside the factory or the department which is supposed to be observed. These cameras are connected with a single monitor or a T.V. set. The views of those cameras are displayed on the monitor and controlled manually by a device (a control) which is designed for this purpose. The views can also be displayed by using automatic control connected to the computer showing views of these cameras in sequence or according to the convenience of the observer.